Multichannel Transcranial Direct Current Stimulation Combined With Treadmill Gait Training in Patients With Parkinson's Disease: A Pilot Study - Na, Yoonju; Kim, Jinuk; Lee, Su-Hyun; Kim, Jihye; Lee, Jungsoo; Shin, Se Young; Chang, Won Hyuk; Cho, Jin Whan; Kim, Yun-Hee (Frontiers in Neurology, 2022)
Background Gait problems are critical impairments in Parkinson's disease (PD) and are related to increased risk of fall and negatively impact activities of daily life. Transcranial direct current stimulation (tDCS) is a non-invasive brain stimulation technique that can modify the cortical excitability of gait-related brain regions. In this study, we investigated whether multichannel tDCS with simultaneous treadmill gait training could improve gait in PD. Methods Twenty-four patients with PD were assigned randomly to a real or sham tDCS group. Before intervention, one patient of the real tDCS group was dropped out, leaving 23 patients to be analyzed in this study. Each patient underwent 30 min of treadmill gait training for 10 sessions over four consecutive weeks. Multichannel 4x1 tDCS was applied using five 6-cm-diameter round electrodes. One anode was placed on the CZ, and four cathodes were positioned symmetrically over the FZ, C5, C6, and PZ. Anodal tDCS (2mA) and sham tDCS were delivered for 20 min. The secondary outcomes were gait performance, as measured by the timed up and go test (TUG) and freezing of gait questionnaire (FOG-Q), and balance was assessed using the dynamic gait index (DGI), Berg balance scale (BBS), and functional reach test (FRT). Motor and non-motor performance of patients with PD were assessed using the Movement Disorder Society-sponsored revision of the Unified Parkinson's Disease Rating Scale (MDS-UPDRS). Participants were assessed before the intervention, immediately after the intervention, and 4 weeks after completion of the intervention. Results The real tDCS group showed a significant improvement in the 10-m walk test, but the sham group did not. Among the secondary outcome measures, MDS-UPDRS part II, TUG, and BBS were improved only in the real tDCS group. Particularly, MDS-UPDRS part II showed a significant group*time interaction effect, indicating that real tDCS demonstrated a better effect on the activities of daily living patients with PD. Conclusions The results of this pilot study suggest that multichannel tDCS applied on the leg motor cortex during treadmill gait training is a safe and effective means to improve gait velocity in patients with PD. Additional rigorous, large-sample, multicenter, randomized controlled trials are needed to confirm the effect of tDCS as a therapeutic adjunct for gait rehabilitation of patients with PD.